Hubungan Stres Kerja dan Kepuasan Kerja yang dimediasi beban kerja pasca pandemi Covid-19 - Pertiwi Sanjiwani, Putu Ari; Rasminingsih, Ni Kadek Nonik; Wibawa, I Wayan Sucipta (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
COVID-19 is a big pandemic that the world is facing. Health organizations are currently in the spotlight. One of them is the organization of the hospital as the main public health service. The front guard of the hospital is a professional nurse. The research objective was to analyze the effect of work stress on job satisfaction with mediation, namely workload at Ari Canti Hospital, Ubud. This research is a quantitative approach, involving a population of 110 nurses selected using a simple random sampling technique. Path analysis is used as an analytical method. Interviews and questionnaires are used as a way of collecting data. The basic theory that underlies the research is the job demands-resources theory. The results of the booking study state that job stress has a significant negative effect on job satisfaction, while the same workload has a clear negative effect on job satisfaction. Workload mediates the effect of job stress on job satisfaction. Mediation is essentially complementary mediation. Workload strengthens the effect of work stress on job satisfaction.